EFL Learners' Motivation and Speech Fluency: The Potential Moderating Effects of Motivation - Sumardi, Yaningsih; Marzuki, Dony; Saptopramono, Hendro; Anggraini, Rina (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2023)
Understanding the connection between EFL learners’ speech fluency and its connection with motivation could provide alternatives for teachers to improve teaching approaches and develop learners’ self-determination. The study investigated the possible connection between motivation and speech fluency among EFL learners. The theoretical framework of self-determination theory and fluency theory was the beacon. While Self-determination theory may shed light regarding the different types of motivation that learners have, fluency theory can provide a base to understand how learners' speech fluency factors may interact with their motivation. A quantitative approach using correlation analysis was employed to collect and analyse data from 54 EFL learners aged 18-25 studying at a vocational university. The administration of a questionnaire to assess learners’ motivation and speech tasks to measure their speech fluency was employed to gather the data. The results show that for EFL learners in the context of the study, their motivation seemed to influence their speech fluency development. These findings contribute to our understanding of the factors that influence speech fluency in EFL learners and have implications for EFL teachers in designing effective pedagogical interventions to enhance students' motivation and speech fluency.